Spirometric changes in children with asthma exposed to environmental tobacco smoke and treated with inhaled corticosteroids - Radic, Snezana; Milenkovic, Branislava; Gvozdenovic, Branislav; Medjo, Biljana; Dimic Janjic, Sanja (Vojnosanitetski pregled, 2021)
Abstract Background/Aim. Corticosteroids are the most frequently prescribed anti-inflammatory treatment in asthma. A purpose of this study was to compare the spirometric parameters as a response to inhaled fluticasone propionate (FP) treatment in children with asthma, exposed and nonexposed to environmental tobacco smoke (ETS). Methods. The study included 527 children aged between 1 and 16 years with persistent asthma divided into the groups of ETS exposed (ETSE, n = 337) and ETS free (ETSF, n = 190) children. Spirometry was performed before (1st set of results) and after 6 months of FP treatment (2nd set of results). Good lung function (GLF) was defined as forced expiratory volume in one second (FEV1) ≥ 85%, and “poor lung function” (PLF) as FEV1
Keywords: asthma; child, preschool; child; adolescent; parents; smoking; tobacco smoke pollution; respiratory function tests; fluticasone; administration, inhalation